On the Determinants of Cross Border Co-operation of Austrian Firms with Central and Eastern European Partners - Peter Huber (Austrian Institute of Economic Research (WIFO), 2003)
We analyse cross-border co-operation of Austrian firms with CEEC partners. Firm size, previous experience with co-operation and depth of integration with the most important partner are more important determinants of co-operation than distance to the closest potential partner. Firms with experience of co-operation are more likely to enter business relationships and less likely not to co-operate. Small firms are unlikely to co-operate in incentive contracts, while firms which are part of production networks typically co-operate in business and ownership relationships. Distance to the closest potential partner increases the probability of not co-operating and reduces the probability of ownership relationships.
Keywords: D23; L10; R12; 330; Cross-Border Cooperation; Internationalisation; Networks; Multinationales Unternehmen; Internationale Unternehmenskooperation; Österreich; Osteuropa